Keseimbangan pasar: Analisis Ekonomi Mikro dalam Menentukan Harga dan Kuantitas Optimum - Matondang, Khairani Alawiyah; Sihotang, Yenni Riski Mutia; Banjarnahor, Olyvia Margaretha; Sitorus, Naomi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Market equilibrium is a fundamental concept in microeconomics that represents a condition where the quantity of goods or services demanded by consumers matches the quantity supplied by producers at a specific price level. This equilibrium occurs at the equilibrium price, reflecting a state where the market faces no pressure to change prices due to the absence of surplus or shortage of goods. This study explains the mechanism of equilibrium formation, the factors influencing it, and the impact of market imbalances, including conditions of excess demand and excess supply, which often compel the market to adapt to price changes. The study highlights that market equilibrium is not a static condition but a dynamic process reflecting the market's response to changes in the economic environment. A deep understanding of market equilibrium is crucial not only for academics but also for policymakers and business practitioners in achieving effective economic stability. The research concludes with a discussion on how markets can return to equilibrium after disturbances and the implications for resource allocation.